Cell suspension culture of aquilaria malaccensis lamk - Siti Zalikha, Binti Mohd Ridzuan Jamil (Universiti Malaysia Sarawak, UNIMAS, 2013)
The genus Aquilaria as it is commonly known as gaharu is a smooth bark tree with aromatic smell. It is under the Thymelaeceae family. The most common species of Aquilaria are A. malaccensis, A. agallocha, A. microcarpa and A. beccariana. It produces resin which has aromatic smell. It will produce gaharu oil when it is infected by the fungi. The economic importance of production of gaharu is medicine, perfume and incense. Much interest has shown to produce gaharu in vitro through tissue culture as the wild supply of the species has been decreased. Nowadays, tissue culture can produce oil of gaharu without planting the tree. In this study, callus of Aquilaria malaccensis was induced for the suspension culture. In the induction of callus, 2.0 mg/L 2,4-Dichlorophenoxyacetic acid (2,4-D) and 0.5 mg/L 6-benzylaminopurine (BAP) was used as the plant growth regulator added to the Murashige and Skoog medium. The growth performance of fully developed callus can be obtained after four weeks of cultured. Cell suspension culture was done with different effect of sucrose and casein hydrolysate concentration. In sucrose effect, 40.0 g/L of sucrose in liquid MS medium enhance the growth of callus while in casein hydrolysate effect, 0.2 g/L, 0.3 g/L and 0.4 g/L could enhance the growth of callus with no difference. Therefore, further research need to be done for promoting the growth of callus.